A high-frequency, low-loss amorphous soft magnetic composite film material and preparation method thereof
Through casting and hot pressing processes, amorphous soft magnetic powder and resin were mixed with the resin to prepare an amorphous soft magnetic composite film with excellent soft magnetic properties, which solved the problem of insufficient Fe content and high hardness of traditional materials, resulting in difficult molding, and realized Preparation of high frequency, high magnetic permeability, and low loss materials.
Patent Information
- Application Number
- CN202210014717.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-01-07
AI Technical Summary
During the preparation process, traditional amorphous soft magnetic materials have problems such as insufficient Fe content and high hardness, which lead to difficulty in forming, making it difficult to meet the needs of MHz high-frequency soft magnetic materials.
Amorphous powder is used for casting and hot pressing. By mixing amorphous soft magnetic powder with resin and additives to form a slurry, casting and drying and stacking hot pressing, amorphous soft soft with excellent soft magnetic properties is prepared. Magnetic composite film.
Amorphous soft magnetic composite film material with high frequency, high permeability and low loss has been realized. The magnetic permeability reaches 8~18 at 200MHz, and the permeability loss angle is less than 0.08. It is suitable for the application of high frequency soft magnetic materials of MHz. .
Smart Images

Figure CN114334347B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an amorphous soft magnetic composite film and a preparation method thereof, and in particular to a high-frequency low-loss amorphous soft magnetic composite film material and a preparation method thereof. The composite film material is a 100 MHz high-frequency soft magnetic material, which can be applied to MHz high-frequency soft magnetic devices, such as electromagnetic shielding, wave absorbing materials, inductance devices, filters, transducers, new magnetic sensors and drivers, etc. Background Art
[0002] Magnetic materials are widely used in the fields of industry, communication and electronic devices. They can be used in various devices such as electromagnetic shielding, wave absorption, energy storage, sensing, filtering, power conversion, etc. These magnetic materials include silicon steel, ferrite, metal magnetic powder, etc. These materials have their own advantages and disadvantages and their own scope of use. With the development of high-power, high-frequency, low-power and integrated electronic devices, these materials can no longer meet the requirements.
[0003] Amorphous soft magnetic materials originated in 1970 and are a relatively new type of soft magnetic material. They have excellent properties such as high frequency, high saturation magnetization, low loss, and high resistance, which provides new materials for the development of high-frequency magnetic electronic devices. The absence of grain boundaries in amorphous magnetic alloys eliminates the pinning effect on the magnetic domain wall, resulting in a decrease in coercivity and improved soft magnetic properties. In the past few decades, people have explored a large number of amorphous soft magnetic materials in multi-component alloy systems, among which Fe, Ni and Co-based amorphous alloys are currently the most mature types. Iron-based amorphous alloys are famous for their abundant natural resources, low material cost and excellent magnetic permeability (μ e ) and saturation flux density (B s ), lower core loss, so it has become the most competitive candidate material. However, traditional amorphous soft magnetic materials are strips prepared by melting and spinning, which are mainly used in motors as a substitute for silicon steel sheets. However, in recent years, with the rise of new fields such as 5G communications, smart applications, the Internet of Things, and smart manufacturing, electronic devices have developed in the direction of high integration, high frequency, and miniaturization. MHz or even hundreds of MHz soft magnetic materials have become a bottleneck in the development of electronic devices. Faced with the urgent demand for MHz high-frequency soft magnetic materials, amorphous soft magnetic materials have also been prepared into powder particles by atomization in recent years. However, the cooling rate of the atomization powder making method is not as fast as the melting and spinning method, which results in a very high amorphous forming ability to produce amorphous soft magnetic powder, which makes the Fe content in amorphous soft magnetic powder not as high as that in amorphous strips. Another problem is that the hardness of amorphous soft magnetic powder is relatively large, which makes the molding of amorphous soft magnetic composite materials very difficult.
[0004] In order to prepare a MHz high-frequency amorphous soft magnetic composite material, the present invention first mixes amorphous soft magnetic powder with resin to prepare slurry, then casts it into a film of a certain thickness, and then prepares the amorphous soft magnetic composite material by a film lamination method. The amorphous soft magnetic film prepared by the present invention has a very high application frequency, its magnetic permeability is above 10 at 200MHz, and its magnetic permeability loss angle is lower than 0.08, and can be widely used in electromagnetic shielding, high-frequency inductance and other fields. Summary of the invention
[0005] The purpose of the present invention is to provide an amorphous soft magnetic composite film with high frequency, high magnetic permeability and low loss. The amorphous soft magnetic composite film is based on amorphous soft magnetic powder, which is mixed with resin and additives to form a slurry of a certain viscosity, and then prepared into an amorphous soft magnetic composite film with certain soft magnetic properties through processes such as cast drying, lamination and hot pressing.
[0006] A specific preparation method of an amorphous soft magnetic composite film material is as follows:
[0007] (1) annealing a certain amount of amorphous powder in a protective atmosphere at 350-660° C. for 0.5-4 hours;
[0008] (2) grinding the powder obtained in step (1) into a uniform powder, or further performing an insulation coating treatment;
[0009] (3) adding a certain amount of resin, silane coupling agent and auxiliary agent to the amorphous powder treated in step (2), and then stirring it evenly by ball milling or sand milling to form a uniform slurry with a certain viscosity;
[0010] (4) casting the slurry treated in step (3) into a film, and then drying the cast film at low temperature to obtain an amorphous soft magnetic film green body, and then laminating the obtained amorphous soft magnetic film green body in multiple layers, and hot pressing them with a flat hot press to obtain an amorphous soft magnetic composite film material;
[0011] Furthermore, the particle size of the amorphous soft magnetic powder is 0.1 to 10 microns, preferably 2 to 7 microns, and the amorphous powder of 2 to 7 microns can also be mixed with the submicron amorphous powder of 100-800 nanometers in a certain proportion, and the mass ratio is 100:10 to 100:0, wherein 0 means that no submicron amorphous powder is contained; the composition of the amorphous soft magnetic material is mainly Fe, and also includes two or more of Si, B, P, Cr, C and other elements, wherein the Fe content is not less than 90wt%;
[0012] Furthermore, the insulating coating layer is one or a composite coating of phosphating coating, NaSiO3 coating, SiO2 coating and silane coating, wherein the coating agent mass content can be 0-5%, 0 means no insulating coating;
[0013] Furthermore, the coupling agent may be a titanate coupling agent or a silane coupling agent;
[0014] Furthermore, the protective atmosphere annealing treatment may be argon, helium, hydrogen, nitrogen or a mixture thereof, and the annealing temperature is preferably 350-550°C;
[0015] Furthermore, the auxiliary agents are thickeners, leveling agents and curing agents; the resin is mainly epoxy resin, which can be multifunctional epoxy, biphenyl epoxy, bisphenol A epoxy, dicyclopentadiene epoxy, and its glass transition temperature is 110-240°C; the curing agent is a latent curing agent, which can be dicyandiamide, adipic acid dihydrazide, modified aliphatic amine curing agent, microcapsule curing agent, organic acid anhydride curing agent, phenolic curing agent, and imidazole curing agent, including methylimidazole, ethylimidazole, phenylimidazole curing agent, and its curing temperature is 80-180°C. The mass ratio of resin to amorphous powder can be preferably 1-6:100; the mass ratio of thickener, leveling agent, curing agent to amorphous powder can be preferably 0.5-2%; there are no specific requirements for thickeners and leveling agents, and they can be selected according to the existing technology and the selected resin.
[0016] Furthermore, the hot pressing temperature is 80-200° C. and the pressure is 10-1000 MPa. Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0017] (1) The present invention adopts amorphous powder to carry out tape casting and hot pressing process to prepare amorphous soft magnetic materials with excellent soft magnetic properties. The process is simple, easy to operate and low in cost. It solves the problem that the current amorphous soft magnetic composite materials are difficult to form due to the high hardness of amorphous particles. In addition, the method is green and environmentally friendly and suitable for large-scale industrial production.
[0018] (2) The thin film prepared by this process has fine amorphous particles and is closely arranged. Its magnetic permeability is between 8 and 18 at 200MHz, and its magnetic permeability loss angle is less than 0.08. It is an excellent soft magnetic material with a loss angle of only 0.08 at 200MHz. This performance is difficult to achieve in other materials. Therefore, this material can be well applied to MHz high-frequency soft magnetic materials.
[0019] (3) According to the application requirements, since the amorphous powder can be subjected to insulation coating treatment, under the coating of the inorganic insulation coating layer, its resistivity increases, resulting in a reduction in eddy current loss, and its cut-off frequency also increases, but the magnetic permeability of the material prepared without the coated powder is higher. The soft magnetic composite material of the present invention is widely used in electromagnetic shielding, wave absorbing materials, inductance devices, filters, transducers, new magnetic sensors and drivers, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 SEM image of amorphous soft magnetic composite film
[0021] Figure 2 Complex permeability diagram of amorphous soft magnetic composite film
[0022] Figure 3 The magnetic loss tangent value of amorphous soft magnetic composite film is shown in Figure 2. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0024] Example 1
[0025] Weigh 60g of 4.5 micron amorphous soft magnetic powder and put it into a nitrogen-filled tubular furnace for annealing at 400℃ for 30min, then put the annealed amorphous powder into a mortar and grind it until it is monodispersed; 1.2g of multifunctional epoxy resin and 0.1g of hydrolyzed silane coupling agent KH550 are uniformly dissolved in acetone solution, then the amorphous powder is dispersed in the epoxy resin solution, and its viscosity is adjusted with acetone to make it a uniform slurry. Then add 0.2g of thickener, 0.3g of leveling agent, and 0.5g of methylimidazole curing agent and stir well, then cast and dry on a casting machine to obtain the required amorphous composite film green body, and laminate the amorphous composite film green body into a whole and heat press and cure it at 80℃. The magnetic permeability of the obtained sample at 100MHz is 9.6, and the loss angle is 0.05; the magnetic permeability of 200MHz is 9.3, and the loss angle is 0.06.
[0026] Example 2
[0027] Weigh 55g of 3.5 micron amorphous soft magnetic powder and 5g of 800 nanometer amorphous soft magnetic powder and put them into a tubular furnace with hydrogen and anneal them at 450℃ for 30min, then put the annealed amorphous powder into a mortar and grind it to monodisperse; dissolve 1g of biphenyl epoxy resin and 0.1g of hydrolyzed silane coupling agent KH560 evenly in acetone solution, then disperse the amorphous powder in the epoxy resin solution, adjust its viscosity with acetone to make it a uniform slurry. Then add 0.2g of thickener, 0.2g of leveling agent, and 0.5g of ethyl imidazole curing agent and stir them evenly, then cast and dry them on a casting machine to obtain the required amorphous composite film green body, and laminate the amorphous composite film green body into a whole and heat press and cure it at 120℃. The magnetic permeability of the obtained sample at 100 MHz is 12.3, and the loss angle is 0.05; the magnetic permeability at 200 MHz is 12, and the loss angle is 0.07.
[0028] Example 3
[0029] Weigh 58g of 3.5 micron amorphous soft magnetic powder and 2g of 100 nanometer amorphous soft magnetic powder and put them into a hydrogen-filled tubular furnace for annealing at 550℃ for 30 minutes, then put the annealed amorphous powder into a mortar and grind it to monodisperse; use silicon dioxide to insulate the amorphous powder by precipitation method; then evenly dissolve 3.5g of bisphenol A epoxy resin and 0.1g of hydrolyzed phthalate coupling agent in acetone solution, then disperse the amorphous powder in the epoxy resin solution, adjust its viscosity with acetone to make it a uniform slurry. Then add 0.15g of thickener, 0.2g of leveling agent, and 1g of phenylimidazole curing agent, stir well, then cast and dry on a casting machine to obtain a layer of amorphous soft magnetic composite film with uniform and smooth surface, and laminate the amorphous composite film green body into a whole and heat press and cure at 150℃. The magnetic permeability of the obtained sample at 100 MHz is 11, and the loss angle is 0.05; the magnetic permeability at 200 MHz is 10.5, and the loss angle is 0.08.
[0030] Example 4
[0031] Weigh 60g of 10-micron amorphous soft magnetic powder and put it into a hydrogen-filled tubular furnace for annealing at 650℃ for 30min, then put the annealed amorphous powder into a mortar and grind it until it is monodispersed; the amorphous powder is insulated and coated with a sodium silicate solution; then 4.5g of dicyclopentadiene epoxy resin and 0.1g of hydrolyzed silane coupling agent KH570 are uniformly dissolved in an acetone solution, and then the amorphous powder is dispersed in the epoxy resin solution, and its viscosity is adjusted with acetone to make it a uniform slurry. Then 0.15g of thickener, 0.1g of leveling agent, and 1g of phenylimidazole curing agent are added and stirred evenly, and then cast and dried on a casting machine to obtain a layer of amorphous soft magnetic composite film green body with uniform and smooth surface, and the amorphous composite film green body is laminated into a whole and hot-pressed and cured at 180℃. The magnetic permeability of the obtained sample at 100 MHz is 10, and the loss angle is 0.04; the magnetic permeability at 200 MHz is 10, and the loss angle is 0.07.
[0032] Example 5
[0033] Weigh 60g of 2-micron amorphous soft magnetic powder and put it into a tubular furnace with hydrogen and anneal it at 430℃ for 30min. Then put the annealed amorphous powder into a mortar and grind it until it is monodispersed; the amorphous powder is insulated and coated with a phosphoric acid solution; then 1.3g of bisphenol A epoxy resin, 0.9g of multifunctional epoxy resin and 0.6g of hydrolyzed silane coupling agent KH550 are uniformly dissolved in a butanone solution, and then the amorphous powder is dispersed in the epoxy resin solution, and its viscosity is adjusted with butanone to make it a uniform slurry. Then add 0.1g of thickener, 0.1g of leveling agent, and 1.5g of phenylimidazole curing agent and stir well, then cast and dry on a casting machine to obtain a layer of amorphous soft magnetic composite film green body with uniform and smooth surface, and laminate the amorphous composite film green body into a whole and heat press and cure it at 150℃. The magnetic permeability of the obtained sample at 100 MHz is 13, and the loss angle is 0.06; the magnetic permeability at 200 MHz is 11, and the loss angle is 0.08.
[0034] Example 6
[0035] Weigh 60g of 5.6 micron amorphous soft magnetic powder and put it into a tubular furnace with hydrogen for annealing at 430℃ for 30min, then put the annealed amorphous powder into a mortar and grind it into monodispersity; the amorphous powder is insulated and coated with phosphoric acid solution; then 1.9g of biphenyl epoxy resin and 0.6g of hydrolyzed silane coupling agent KH550 are uniformly dissolved in butanone solution, and then the amorphous powder is dispersed in the epoxy resin solution, and its viscosity is adjusted with butanone to make it a uniform slurry. Then add 0.05g of thickener, 0.1g of leveling agent, and 0.1g of methylimidazole curing agent and stir well, then cast and dry on a casting machine to obtain a layer of amorphous soft magnetic composite film green body with uniform and smooth surface, and the amorphous composite film green body is laminated into a whole and hot pressed and cured at 180℃. The magnetic permeability of the obtained sample at 100 MHz is 14, and the loss angle is 0.06; the magnetic permeability at 200 MHz is 11, and the loss angle is 0.08.
[0036] Example 7
[0037] Weigh 57g of 4.6 micron amorphous soft magnetic powder and 3g of 300 nanometer amorphous soft magnetic powder and put them into a tubular furnace with hydrogen and anneal them at 430℃ for 30min. Then put the annealed amorphous powder into a mortar and grind it to monodisperse. Then, insulate and coat the amorphous powder with a phosphoric acid solution. Then, evenly dissolve 1.6g of multifunctional epoxy resin and 0.6g of hydrolyzed silane coupling agent KH570 in a butanone solution. Then, disperse the amorphous powder in the epoxy resin solution and adjust its viscosity with butanone to make it a uniform slurry. Then, add 0.05g of thickener, 0.05g of leveling agent, and 0.2g of ethyl imidazole curing agent and stir them evenly. Then, cast and dry them on a casting machine to obtain a layer of amorphous soft magnetic composite film green body with uniform and smooth surface. The amorphous composite film green body is laminated into a whole and hot-pressed and cured at 120℃. The magnetic permeability of the obtained sample at 100 MHz is 15, and the loss angle is 0.04; the magnetic permeability at 200 MHz is 10, and the loss angle is 0.08.
Claims
1. A method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material, characterized in that: The material is prepared from amorphous powder as raw material, and after pretreatment, a green body is prepared by a tape casting process, and then the green body is stacked and hot pressed; the loss angle of the material is less than 0.08 at a frequency of 1MHz to 200MHz; The preparation method thereof comprises: (1) Annealing the amorphous soft magnetic powder in a protective atmosphere at 350~660℃ for 0.5~4 hours; (2) grinding the powder obtained in step (1), or subsequently subjecting the obtained powder to an insulation coating treatment; (3) adding the amorphous powder treated in step (2) to the resin, coupling agent and auxiliary agent, and then stirring evenly by ball milling or sand milling to form a uniform slurry; (4) casting the slurry treated in step (3) into a film, and then drying the cast film to obtain an amorphous soft magnetic film green body, and then laminating the obtained amorphous soft magnetic film green body in multiple layers, and hot pressing them with a flat hot press to obtain a high-frequency low-loss amorphous soft magnetic composite film material; The amorphous soft magnetic powder is obtained by mixing amorphous powder with a particle size of 2 to 7 microns and submicron amorphous powder with a particle size of 100 to 800 nanometers in a mass ratio of 100:10 to 29:1; the amorphous soft magnetic powder is mainly composed of Fe and also includes two or more of Si, B, P, Cr, and C elements, wherein the Fe content is not less than 90wt%; The hot pressing temperature is 80-200° C., and the pressure is 10-1000 MPa.
2. The method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material according to claim 1, characterized in that: The insulating coating layer is one or more composite coatings of phosphating coating, NaSiO3 coating, SiO2 coating and silane coating.
3. The method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material according to claim 1, characterized in that: The coupling agent is a titanate coupling agent or a silane coupling agent.
4. The method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material according to claim 1, characterized in that: The protective atmosphere in step (1) is a mixture of one or more of argon, helium, hydrogen and nitrogen, and the annealing temperature is 350-550°C.
5. The method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material according to claim 1, characterized in that: The auxiliary agents are thickeners, leveling agents and curing agents, the resin is epoxy resin, and the curing agent is a latent curing agent.
6. The method for preparing a high-frequency, low-loss amorphous soft magnetic composite film material according to any one of claims 1 to 5, characterized in that: The material is used in high-frequency soft magnetic devices of MHz and above.
Citation Information
Patent Citations
Tape-casting temperature isostatic pressing composite molding preparation method of metal soft magnetic composite material
CN104036906A
Preparation method of magnetic material
CN108597713A